Karaktersitik Lahan Agroforestri - Fahruni Fahruni (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2017)
Soil quality can be maintained through wise land use. Agroforestry is a solution for land use that keeps soil fertility at the moment. Land use through this agroforestry combines forestry crops with agriculture and/or livestock on a rotating or alternating land. The purpose of this research is to know soil characteristics in rubber agroforestry pattern (Hevea brasiliensis Muell, Arg.). As an interrupted plant Arachis hypogeae. This study was conducted with soil analysis before and after intercropping. Comparing the composition and value of macro nutrient content. Soil characteristics after agroforestry exploitation can be seen from the improvement of macro nutrients, namely: N elements increased from 0.16 mg/100gr to 0.45 mg/100gr. Element P increased from 5.57 to 8.93. For element K of 15.87 increased to 41.50 and organic C increased from 0.83 to 1.55.